Detection of foreign bodies in canned foods using ultrasonic testing - Hrairi, Meftah; Elias, M. A. (2011)
Foreign bodies in packaged foods may pose both a safety risk and a risk of perceived degradation of quality. Foreign bodies could be small metallic or nonmetallic pieces that are accidentally dropped into the food products. In this paper, the ultrasonic method is used to detect the foreign bodies in canned foods. In order to establish a technical concept for the detection of foreign bodies in canned foods, an experimental investigation was carried out using pulse-echo ultrasonic testing. A number of simulated foreign object pieces were deliberately put inside the canned food and the results were analyzed. The approach demonstrates that ultrasound has potential for application in many industrial food packaging environments where foreign objects need to be detected.